Pelatihan Pengolahan Minyak Goreng Bekas (Minyak Jelantah) Menjadi Sabun Padat Bagi UMKM dan IRT di Desa Sidosari, Kecamatan Natar, Kabupaten Lampung Selatan - Ginting, Simparmin; Hanif, Muhammad; Damayanti, Sri; Hermida, Lilis (FT Universitas Lampung, 2021)
This community service aims to help the UMKM engaged in the food industry in Sidosari Village, Natar District, South Lampung Regency (partners). Partners never replace used cooking oil (waste cooking oil) with new ones, but only add new oil to used cooking oil for frying the next food. Partners consider that using used cooking oil from branded cooking oil will be safe to use many times, thereby saving on expenses without knowing the consequences. This understanding is due to the partner's low level of awareness. Therefore, the community service (PkM) is very appropriate for understanding partners about the dangers of waste cooking when used repeatedly without ever being replaced with a new one. The methods used in this service include: socialization, training, and direct practice of processing and making eco-friendly handmade solid laundry soap from used cooking oil. Socialization has been explained the dangers of using cooking oil for health and the environment. Training and practice were provided to partners on how to process and make eco-friendly handmade solid laundry soap made from used cooking oil and bath soap from new oil for household use and even for sale. After participating in this service, residents and the UMKM in particular no longer used cooking oil repeatedly to fry their products to increase product quality. They are enthusiastic to continuously make solid soap from used cooking oil for washing purposes and even make it from new oil for bath soap purposes. Thus, it will save the cost of shopping for laundry soap and bath soap reduce dependence on manufacturer's soap so that the environment is not polluted by detergent waste. It can even be an additional income for those who are serious about getting into the business of making this laundry soap and environmentally friendly homemade bath soap.